Madame de Genlis on the Victorian Stage - Juan Manuel Ibeas Altamira (Cahiers Victoriens et Edouardiens)
This study analyses the works by Madame de Genlis and their connections to Victorian theatre. Over the course of her long and prolific career, Stéphanie Félicité du Crest de Saint-Aubin, Comtesse de Genlis, produced an immense collection of works that include pedagogical texts, novels, plays, and short stories. All of her books were well received in Europe because they presented the new pedagogical ideas of the French Enlightenment but without the concepts and thoughts associated to the Revolution. Even if in Britain Madame de Genlis was best known for her children’s books, her legacy could be triply conceived as that of an educator, moralist, and playwright. Such roles appeared in her first text translated into English, Theatre of Education. The book appeared in print in 1781, a year after having been published in France, which shows the interest that English readers had towards her work and the type of dramatic pieces she developed. Such interest in this author did not falter during the Victorian period. In contrast, her moral and monarchic tendencies, together with her exaltation of the personal effort to face adversity and rise up the social ladder, made her a model of the new world order. Queen Victoria’s first visit was to see the Siege of Rochelle, adapted from Genlis’s story Le siège de La Rochelle. Beyond an aristocratic audience, other types of theatre-goers’ sensibilities were alluded to in plays such as The Palace of Truth, W. S. Gilbert’s adaptation of Madame de Genlis’s fairy tale, Le palais de vérité. The play ran for approximately 140 performances, toured the British provinces, and enjoyed various revivals. Madame de Genlis’s popularity, however, did diminish in the late nineteenth century, as Victorian critics’ contempt for her work overpowered public opinion. This study offers an analytic historiographical revision of Madame de Genlis’s relevance to Victorian theatre and of the type of criticism her influence generated.